Strengths and Weaknesses of Family Leisure in Adolescents - Hernández-Prados, Mª Ángeles; Álvarez-Muñoz, José Santiago (Italian Sociological Review, 2026)
The increase in shared family time has reopened the debate on family leisure and its educational potential. However, most studies have focused primarily on quantification, without adequately assessing the quality of these practices. The aim of this descriptive, inferential, quantitative, cross-sectional, and non-experimental study is to identify and delimit the weaknesses and strengths that adolescents attribute to family leisure. A descriptive study was conducted with a sample of 1,054 students from the seventh to tenth grades in seven Spanish high schools, who completed the questionnaire “Evaluation of Family Leisure Practices. Questionnaire for Adolescents.” The results highlight improved communication and family bonding as the main strengths, while repetition and routine family traditions emerge as the primary weaknesses. Moreover, the findings indicate that grade level, age, nationality, mother’s nationality, family structure, and academic performance are significant variables in the perception of strengths, whereas gender, grade level, age, and mother’s educational level are significant for the perception of weaknesses. These results suggest that the implementation of family leisure as an educational resource requires counselling and guidance in order to minimize risks and maximize opportunities. Preventive actions should also be established to counteract family disengagement as adolescents grow older.